Introduction - Sasamal T.N.; Singh A.K.; Mohan A. (My University, 2025)
The exponential decrease in feature size causes serious challenges in CMOS technology due to oxide thickness, diffusion barriers, power dissipation, and leakage currents, etc. © Springer Nature Singapore Pte Ltd 2020.